Hypoxia Promotes Pancreatic Cancer Cell Dedifferentiation to Stem-Like Cell Phenotypes With High Tumorigenic Potential by the HIF-1α/Notch Signaling Pathway. Issue 5 (May 2021) - Mu, Rui; Zou, Yong-Kang; Tu, Kui; Wang, Dian-Bei; Tang, Dan; Yu, Zhou; Zhao, Lijin
Abstract : Objectives: This study aimed to investigate the effect and mechanism of hypoxia on pancreatic cancer (PC) cell dedifferentiation and tumorigenic potential. Methods: Inhibition of hypoxia-inducible factor 1α (HIF-1α) and overexpression of Notch1 in PC HS766T cell lines were by lentiviral transfection. The expression of stem cell-specific markers C-X-C motif chemokine receptor 4, CD44, and Nestin was detected by immunofluorescence and Western blot assays. Cell invasion capacity was examined by Transwell assay. Tumorigenic potential was measured in an in situ tumor transplantation experiment. The expression of HIF-1α, Notch signals, and apoptosis signals was examined by Western blot assay. Results: Hypoxia promoted PC cells to dedifferentiate into stem-like cells by upregulating HIF-1α and activating Notch signals. Silencing of HIF-1α significantly repressed cell dedifferentiation and invasion, whereas overexpression of Notch1 reversed the effect of HIF-1α repression. In situ tumor transplantation experiment further confirmed that hypoxia promoted tumorigenic ability through upregulating HIF-1α. Moreover, the expression of HIF-1α and Notch1 was significantly increased in human PC tissues, and high expression of HIF-1α was correlated with poor survival rate. Conclusions: Hypoxia promoted PC cell dedifferentiation to stem-like cell phenotypes with high tumorigenic potential by activating HIF-1α/Notch signaling pathway, indicating a novel role in regulating PC progression.